Do obese patients with type A aortic dissection benefit from total arch repair through a partial upper sternotomy? - Xie, Lin-Feng; He, Jian; Wu, Qing-Song; Qiu, Zhi-Huang; Jiang, De-Bin; Gao, Hang-Qi; Chen, Liang-wan (Frontiers in Cardiovascular Medicine, 2023)
Background：There are few reports of total arch replacement through a partial upper sternotomy in obese patients with type A aortic dissection, and the safety and feasibility of this procedure still need to be further investigated. The present study also sought to investigate the potential clinical advantages of using a partial upper sternotomy for total arch replacement in obese patients compared with conventional full sternotomy for total arch replacement. Methods：This is a retrospective study. From January 2017 to January 2020, a total of 65 obese patients underwent total arch replacement with triple-branch stents. Among them, 35 patients underwent traditional full sternotomy and 30 patients underwent partial upper sternotomy. The perioperative clinical data and postoperative follow-up results of the two groups were collected, and the feasibility and clinical effect of PUS in total arch replacement in obese patients were summarized. Results：The in-hospital mortality rates of the two groups were similar. The total operative time, cardiopulmonary bypass (CPB) time, aortic cross-clamp (ACC) time, cerebral perfusion time, and deep hypothermic circulatory arrest (DHCA) time were similar in both groups. The thoracic drainage volume and postoperative red blood cell transfusion in PUS group were significantly lower than those in FS group. In PUS group, the time of mechanical ventilation was shortened, and the incidence of pulmonary infection, hypoxemia and sternal diaphoresis was lower. Conclusions：This study shows that total arch replacement surgery through a partial upper sternotomy in obese patients is a safe and effective procedure. It is superior to FS in terms of blood loss, postoperative blood transfusion, and respiratory complications.